Perancangan Sistem Informasi Pendukung Keputusan Untuk Menentukan Kelayakan Mahasiswa Tinggal di Luar Asrama (Studi Kasus : Universitas Advent Indonesia) - Rendi Ronaldo; Elmor Benedict Wagiu (TeIKa, 2019)
Decision support system is a system that provide problem solving, where the users of the system can choose the best alternative decision. In making the decision there are many things must be considered so that the decision taken is the right one. Universitas Advent Indonesia is one of the universities that provides a dormitory as a residence for the students. Besides dormitories, the students can also reside outside the dormitory. To be able to reside outside, students must register themselves and the Student Affairs Bureau decides who is the student that meet the qualification. There is a problem faced by the Student Affairs Bureau where there is a difficulty to finalize the decision whether students are eligible or not. To occupy the problem, a decision support system is designed to verify the eligibility of students. The requirements that have been decided for the students to be able to reside outside are stay at the lecturer’s house, have been married, stay with their parents or their siblings, the nurses students that have taken the professional nurses and the senior students that do not longer have any subject besides thesis. This research used Forward Chaining method and in designing the system the web-based will be employed. The result of this study can be used as a tool in making decision to determine the eligibility of the students to reside outside.